The feasibility and safety of simultaneous bilateral video-assisted thoracic surgery for the treatment of bilateral pulmonary lesions - Tao, Xiandong; Zhao, Jiannan; Wei, Wei; Shan, Zhengxiang; Zheng, Hongyang; Pan, Tiewen (Frontiers in Oncology, 2022)
Background The aim of this study was to evaluate the feasibility and safety of simultaneous bilateral video-assisted thoracic surgery (VATS) for the treatment of bilateral pulmonary lesions. Methods The data of 11 patients who received simultaneous bilateral pulmonary surgery using VATS in the Department of Thoracic Surgery of The Third Affiliated Hospital of Naval Medical University between January 2016 and August 2021 were retrospectively analyzed. Results The cases of four male and seven female patients, with a mean age of 57.54 ± 8.37 years (range, 44-67 years), were reviewed. Nonanatomic wedge resection, pulmonary segmentectomy or lobectomy via VATS were performed depending on each patient’s situation. Mean 1 second forced expiratory volume (FEV1) was 2.55 ± 0.66 L(range, 1.49-3.88 L), mean intraoperative bleeding volume was 91.81 ± 49.56 mL(range, 30-150 mL), mean operating time was 273.72 ± 68.98 min(range, 132-390 min), and mean drainage duration was 5.27 ± 3.60 days(range, 2-14 days), with a mean total drainage volume of 1,515.90 ± 772.75 mL(range, 530-3,225 mL). Only one postoperative complication (air leakage) occurred, with an overall complication rate of 9.09%. The mean postoperative hospital stay was 8.81 ± 3.60 days (range, 5-18 days), and the mean total cost of hospitalization was 67,054.53 ± 20,896.49 RMB (range, 47,578.45-123,530.8 RMB). Conclusions Simultaneous bilateral pulmonary surgery using VATS for the treatment of bilateral pulmonary lesions is safe and feasible and can therefore be considered after strict preoperative evaluation of the patient.